2015
DOI: 10.1016/j.virusres.2014.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Theiler's virus-induced apoptosis in infected murine macrophages results in necroptosis

Abstract: In mice Theiler’s murine encephalomyelitis virus (TMEV) persists in macrophages that eventually undergo apoptosis. TMEV infection of macrophages in culture induces apoptosis through the intrinsic pathway, restricting virus yields. We show that inhibition of TMEV-induced apoptosis leads to phosphorylation of receptor interacting protein 1 (RIP1), localization of RIP1 and RIP3 to mitochondria, ROS production independent of MAPK activation and programmed necrosis (necroptosis). Blocking both apoptotis and necropt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…In the present study, inhibition of apoptosis using the pan-caspase inhibitor (Z-VAD-FMK) increased RVA replication, indicating that RVA-induced apoptosis is a host defense mechanism. This result is in agreement with the findings of studies in which the inhibition of TMEV- and HIV-1-induced apoptosis of infected murine macrophages and CD4 T lymphocytes, respectively, induced a transition from apoptosis to necroptosis and resulted in significantly higher viral titers ( 49 , 50 ). Taken together, our data suggest that the RVA-induced RIPK1-dependent pathway acts as a proviral mechanism that promotes viral replication and/or spread, whereas—consistent with the findings of a previous study ( 56 )—RVA-induced apoptosis is an antiviral strategy that restricts viral replication.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, inhibition of apoptosis using the pan-caspase inhibitor (Z-VAD-FMK) increased RVA replication, indicating that RVA-induced apoptosis is a host defense mechanism. This result is in agreement with the findings of studies in which the inhibition of TMEV- and HIV-1-induced apoptosis of infected murine macrophages and CD4 T lymphocytes, respectively, induced a transition from apoptosis to necroptosis and resulted in significantly higher viral titers ( 49 , 50 ). Taken together, our data suggest that the RVA-induced RIPK1-dependent pathway acts as a proviral mechanism that promotes viral replication and/or spread, whereas—consistent with the findings of a previous study ( 56 )—RVA-induced apoptosis is an antiviral strategy that restricts viral replication.…”
Section: Discussionsupporting
confidence: 92%
“…The transition from apoptosis to necroptosis and vice versa has been reported in response to HIV-1 infection, Theiler’s murine encephalomyelitis virus (TMEV) infection, and tunicamycin stimulation ( 49 , 50 , 57 ). Our results suggested that the decrease in RVA titers in response to the downregulation of the necroptosis molecules, RIPK1, RIPK3, and MLKL, could be attributed to protection from cell death, induction of apoptosis, or both mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al examined TNF-induced necrosis in NIH 3T3 cells and showed that RIP3 regulates TNF-induced ROS overproduction by activating metabolic enzymes, leading to necrosis via damaging of cellular membranes and organelles [ 12 ]. Son et al [ 13 ] showed that Nec-1 can significantly reduce ROS production in Theiler’s murine encephalomyelitis virus (TMEV)-infected macrophages. Our previous studies showed that Timosaponin B-II, an anti-oxidative monomer extracted from Rhizoma anemarrhenae , reduced retinal ganglion cell-5 (RGC-5) cell necroptosis by inhibiting ROS accumulation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, apoptosis may be regulated at the genetic level due to the expression of certain viral proteins or the triggering of novel genes (28,29). In recent years, specifically infecting tumor cells with viruses to induce apoptosis became an important aspect of cancer biotherapy, thus further manipulating tumor development (18,30).…”
Section: Discussionmentioning
confidence: 99%